104k views
1 vote
What is the difference when 3x2 − 2x + 7 is subtracted from 5x3 - 4x2 +10

A) 5x3-7x2+2x+3
B). 5x3+x2+2x-3
C) 5x3-7x2+2x +17
D) 5x3+x2+2x+17

User Christo
by
5.1k points

1 Answer

5 votes

Answer:


f(x) -g(x) =(5x^3) +(-4x^2- 3x^2) + (0+2x) +(10-7)

And if we simplify we got:


f(x) -g(x) =5x^3 -7x^2 +2x+ 3

And the best option for this case is:

A) 5x3-7x2+2x+3

Explanation:

For this case we have this function given:


f(x) = 5x^3 -4x^2 +10

And we want to subracr from the last function this one:


g(x) =3x^2 -2x+7

So we want to find
f(x)-g(x) and replacing we got:


f(x) -g(x) =(5x^3 -4x^2 +10) -(3x^2 -2x +7)

And if we aggrupate the terms we got:


f(x) -g(x) =(5x^3) +(-4x^2- 3x^2) + (0+2x) +(10-7)

And if we simplify we got:


f(x) -g(x) =5x^3 -7x^2 +2x+ 3

And the best option for this case is:

A) 5x3-7x2+2x+3

User Nick Zimmerman
by
5.9k points